Pengaruh Pemberian Ekstrak Etanol Kulit Buah Jeruk Baby (Citrus sinensis L. Osbeck) Selama 28 hari terhadap Kadar SGOT dan SGPT - Sofia, Vivi; Widyaningsih, Wahyu; Yuliani, Sapto; Bachri, Moch Saiful (Jurnal Sain Veteriner, 2024)
One of the plants used as natural medicine is baby orange (Citrus sinensis L. Osbeck). Baby oranges contain hesperidin, hesperetin, narirutin and nobiletin compounds. The purpose of this study was to determine the effect of giving ethanol extract of baby orange peel for 28 days on liver function as seen from the increase in SGOT and SGPT levels. This research is a pure experimental study with a completely randomized design (CRD) with a unidirectional pattern, namely the method used to observe the relationship of independent variables (including: normal control, negative control, ethanol extract of baby orange peel (EEKBJB) doses of 50, 100, 200 and 400 mg/kg BW) with the dependent variable (SGOT and SGPT levels). The test animals used in this study were 30 male Wistar rats which were divided into 6 treatment groups which were treated for 28 consecutive days. On day 29, blood samples were taken from the orbital sinus of the eye and the levels of SGOT and SGPT were measured. There was a significant difference in the levels of SGOT and SGPT as indicated by the results of the One Way ANOVA test (p<0.05). The results of the Post Hoc-Tukey test for SGOT levels showed a significant difference between the control group and the 50 mg/kg BW dose group, while the 100, 200 and 400 mg/kg BW doses did not show a significant difference. The results of the Post Hoc-Tukey, s-HSD test for SGPT levels did not show a significant difference between the control group and the 50, 100, 200 and 400 mg/kg BW dose groups. Significant differences were shown by doses of 50 and 400 mg/kg BW. Giving EEKBJB for 28 days did not cause toxic effects on liver function, seen from the absence of an increase in SGOT and SGPT levels.